2020
DOI: 10.19184/wrtp.v14i4.19726
|View full text |Cite
|
Sign up to set email alerts
|

Mengajar Engineering Design Process Untuk Memperkenalkan STEM Pada Siswa Madrasah Ibtidaiyah Raudhatul Qur’an

Abstract: Saat ini, pekerjaan di industri yang tumbuh paling cepat didominasi dengan pekerja dengan keterampilan Sains, Teknologi, Teknik, dan Matematika (STEM). Untuk menjadi kompetitif, penyedia pekerjaan membutuhkan tenaga kerja yang dapat beradaptasi dengan tempat kerja yang berubah. STEM memberdayakan individu dengan keterampilan untuk sukses dan beradaptasi dengan dunia yang terus berubah tersebut. Dengan latar tersebut di lakukan kegiatan pengabdian masyarakat dengan nama pelatihan Tech for Kids (TFK), yang menit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Some studies that apply EDP have benefited positively for students. Among them, research conducted by [66], found that the Engineering Design Process (EDP) conducted in the form of Tech for Kids (TFK) training activities can increase knowledge, mastery of technology, foster broad thinking skills, increase students" desire when learning, and increase student achievement in school. [67] also conducted research on Agriscience-based EDP learning models with STEM approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies that apply EDP have benefited positively for students. Among them, research conducted by [66], found that the Engineering Design Process (EDP) conducted in the form of Tech for Kids (TFK) training activities can increase knowledge, mastery of technology, foster broad thinking skills, increase students" desire when learning, and increase student achievement in school. [67] also conducted research on Agriscience-based EDP learning models with STEM approaches.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, engineers should investigate and find alternative solutions when facing problems and challenges. Engineers must solve problems with various techniques using either a direct solution or many other alternative solutions (Nusyirwan et al, 2020). The following is an example of students' responses to adapting indicators.…”
Section: Figure 5 Example Of Final Trial the Prototypementioning
confidence: 99%